1983
DOI: 10.1126/science.6849138
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinic Acid: An Endogenous Metabolite That Produces Axon-Sparing Lesions in Rat Brain

Abstract: A current hypothesis links the neuroexcitatory properties of certain acidic amino acids to their ability to cause selective neuronal lesions. Intracerebral injection of the neuroexcitatory tryptophan metabolite, quinolinic acid, has behavioral, neurochemical, and neuropathological consequences reminiscent of those of exogenous excitotoxins, such as kainic and ibotenic acids. Its qualities as a neurotoxic agent suggest that quinolinic acid should be considered as a possible pathogenic factor in neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
472
1
9

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,197 publications
(494 citation statements)
references
References 33 publications
12
472
1
9
Order By: Relevance
“…Quinolinic acid (QA) is an agonist of NMDA receptors and is widely used in experiments to induce excitotoxicity. 11 In the literature, we have found reports of reduced susceptibility to neural damage in six mouse HD models. We have also identified studies on an additional six models where susceptibility to excitotoxicity was not different from that seen in wild-type control mice.…”
Section: Huntingtin Mediates Reduced Susceptibility Against Excitotoxmentioning
confidence: 98%
“…Quinolinic acid (QA) is an agonist of NMDA receptors and is widely used in experiments to induce excitotoxicity. 11 In the literature, we have found reports of reduced susceptibility to neural damage in six mouse HD models. We have also identified studies on an additional six models where susceptibility to excitotoxicity was not different from that seen in wild-type control mice.…”
Section: Huntingtin Mediates Reduced Susceptibility Against Excitotoxmentioning
confidence: 98%
“…The magnitude of this death event is increased in both structures after early (PND7) excitotoxic quinolinic acid (QA) injury to the striatum (Macaya et al, 1994). This lesion spares the terminals of the nigrostriatal dopaminergic projection (Schwarcz et al, 1983;Macaya and Burke, 1992). In both structures, the morphology of the induced death event is apoptotic and indistinguishable from natural cell death.…”
mentioning
confidence: 90%
“…This decrease occurs despite the axon-sparing nature of this injury (Schwarcz et al, 1983;Macaya and Burke, 1992) and in the absence of any direct injury to the SN. We have also shown that natural cell death occurs within the SN pars compacta (SNpc) (Janec and Burke, 1993), with the morphology of apoptosis (Kerr et al, 1972), and that this death event is augmented after excitotoxic (Macaya et al, 1994) injury to the striatum during development.…”
mentioning
confidence: 92%
“…[20][21][22] Overstimulation of NMDA receptors leads to neuronal damage. 23 Neurotoxicity of KYN and its metabolites has been demonstrated in animal studies 19,20,24 and studies using human cell cultures. 25,26 KYN is able to pass the BBB 27 and human microglia have been shown capable of metabolizing this substance into its toxic metabolites.…”
mentioning
confidence: 99%